1951
DOI: 10.1177/004051755102100205
|View full text |Cite
|
Sign up to set email alerts
|

Types and Dimensions of Fiber Scales from the Wool Types of Domestic Sheep and Wild Life

Abstract: Scale structure and dimensions and fiber thickness were measured on a number of fibers repre senting the different fiber types from fleeces of several wild life species, including the Big Horn sheep, and of fibers from the various wool types of domestic and primitive sheep, including the fine-wool, medium-wool, long-wool, and mixed-wool types. The scale index, or relation of scale height to fiber thickness, was studied as a means of identification of fiber types and as a breed characteristic. The relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

1954
1954
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
2
3
1
Order By: Relevance
“…The number of scales per 100 µm is 8.6 and 8.4 and the scale height 18.96 μm and 18.27 μm, respectively, for raw and pulled wool. These results are in agreement with those of Mahal et al [20]. In their investigation, they proved that the average number of scales per 100 µm for medium wool is approximately eight.…”
Section: Sem Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The number of scales per 100 µm is 8.6 and 8.4 and the scale height 18.96 μm and 18.27 μm, respectively, for raw and pulled wool. These results are in agreement with those of Mahal et al [20]. In their investigation, they proved that the average number of scales per 100 µm for medium wool is approximately eight.…”
Section: Sem Analysissupporting
confidence: 93%
“…The scale index, which is the ratio of scale height to fiber diameter [20], is equal to 0.743 for raw wool and 0.703 for pulled wool. Figure 2c, which presents raw wool, and Figure 2d, which presents the fiber after alkali treatment, show that scales height decreased, and as a result the scale index decreased.…”
Section: Sem Analysismentioning
confidence: 99%
“…On the other hand, it is apparent that as fibre diameter increased, scale type tended to become imbricate. This result conforms with the findings of Mahal et al (1951) who found that as the diameter increases, the scales become imbricate. Frequency of shearing was found to have highly significant (P < 0.01) effect on type of scaliness in fine fibres and a non-significant effect on type of scaliness of the coarse fibres (Table 2).…”
Section: (B) Type Of Scaliness :-supporting
confidence: 93%
“…The corresponding values of Ossimi fleeces were 8.36 and 7.00 for fine and coarse wool fibres, respectively . These values are higher than those reported by Mahal et al (1951) who found that the average number of Sc/100 µ was 7.2 on the wool fibres, 5.3 on the hair fibres and 6.8 on the kemp fibres. On the other hand, the present values are less than those suggested by Mathews (1947) who reported that the average Sc / 100 µ ranged from 10 to 12 in fine wool fibres.…”
Section: Resultscontrasting
confidence: 71%
“…The edges of the scales in the coronal pattern face away from the fibre axis and tend to grow around the fibre in a semi-circle. Wool fibres with a diameter of less than 25 µm show coronal pattern of scales 23 . Reticulate type scales are irregular in size and shape and appear randomly distributed on the surface of the fibre.…”
Section: Introductionmentioning
confidence: 99%